Peranan Work Ethics Karyawan Terhadap Subjective Well-Being Pada Perusahaan Keluarga Di Indonesia - Tan Evan Tandiyono (Transformasi: Journal of Economics and Business Management, 2023)
The research objectives to be achieved in accordance with the formulation of the problem described above are to find out, analyze and answer the role of Employee Work Ethics on Subjective Well-Being in Family Companies in Indonesia. This study took respondents from all existing employees at PT Surya Polyplas Utama, with a total of 109 people. In carrying out the field, this study took primary data by using a questionnaire. This type of research that will be used is to use quantitative research methods with explanatory methods. The end result of this research is a picture of a causal relationship, so this method uses samples and hypotheses. The analysis technique used is multiple linear regression analysis and path analysis to test the hypothesis. While the classic assumption test used includes Multicollinearity Test, Heteroscedasticity Test, Autocorrelation Test, and Data Normality Test. Overall, the indicators used in this study are valid (because the correlation coefficient is > 0.200 with a significance level of <0.05) and reliable (because the coefficient value of Cronbach's Alpha is > 0.60). The results of the classical assumption test also show that this research has fulfilled, among others 1.) Both regression models are free from multicollinearity; 2.) There is no heteroscedasticity; 3.) There is no autocorrelation in both regression models; and 4.) The residuals of the two regression models are normally distributed. The findings of the analysis using path analysis while answering the hypothesis concluded that the influence of employee work ethics on subjective well-being is significant, with a value of Standardized coefficients Beta 0.746 with a significance level of 0.000.